Maternal oral-gut microbiome and artificial assisted reproduction - YANG Peiyue, PENG Xian, ZHOU Xuedong (Kouqiang yixue)
Oral and intestinal microbiota are two of the most complex microbiota in the human body which play important roles in maintaining various physiological balances. Assisted reproductive technology(ART)is an in vitro treatment of gametes and embryos to help women conceive and produce healthy fetuses. Current assisted reproductive technology ART includes in vitro fertilization with or without oocyte intracytoplasmic sperm injection(IVF/ICSI). The ectopic colonization of oral-gut microbiota, their metabolites, and immune regulation mechanisms may affect the outcomes of assisted reproduction. This article mainly reviews the ways, mechanisms and potential beneficial interventions of oral and intestinal microbiota on women receiving artificial assisted reproductive therapy.